2012
DOI: 10.1128/aac.05996-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergy of Colistin Combinations against Colistin-Resistant Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae Isolates

Abstract: Colistin resistance, although uncommon, is increasingly being reported among Gram-negative clinical pathogens, and an understanding of its impact on the activity of antimicrobials is now evolving. We evaluated the potential for synergy of colistin plus trimethoprim, trimethoprim-sulfamethoxazole (1/19 ratio), or vancomycin against 12 isolates of Acinetobacter baumannii (n ‫؍‬ 4), Pseudomonas aeruginosa (n ‫؍‬ 4), and Klebsiella pneumoniae (n ‫؍‬ 4). The strains included six multidrug-resistant clinical isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 23 publications
4
74
2
5
Order By: Relevance
“…The effect of colistin in antibiotic combination is based on its detergent-like property: it interacts with surface LPS A. baumannii 9 (45) 11 (55) and phospholipids, disturbing membrane permeability. Colistin exposure leads to increased permeability to large or hydrophobic compounds such as SXT (8). Synergic effect of colistin and SXT against S. maltophilia was found in 47% of isolates by Giamarellos-Bourboulis et al (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of colistin in antibiotic combination is based on its detergent-like property: it interacts with surface LPS A. baumannii 9 (45) 11 (55) and phospholipids, disturbing membrane permeability. Colistin exposure leads to increased permeability to large or hydrophobic compounds such as SXT (8). Synergic effect of colistin and SXT against S. maltophilia was found in 47% of isolates by Giamarellos-Bourboulis et al (13).…”
Section: Discussionmentioning
confidence: 99%
“…Stenotrophomonas maltophilia isolates were tested in 7 doubling dilutions of colistin and 11 doubling dilutions of SXT, whereas P. aeruginosa and A. baumannii strains were tested in 7 doubling dilutions of SXT and 11 doubling dilutions of colistin. Microbroth plates When synergy was detected by CB, a time-kill assay (TKA) was performed at 1xMIC following a previously published method (8). When MICs were above the therapeutic level, SXT was used at 8 mg/L and colistin at 4 mg/L, which fits the peak serum levels of these agents (9).…”
Section: Methodsmentioning
confidence: 99%
“…Vidaillac ve ark. (28) yaptıkları in vivo çalışmada kolistin dirençli A.baumannii, Pseudomonas aeruginosa ve Klebsiella pneumoniae suşlarında kolistin-SXT kombinasyonunun sinerjik etki gösterdiğini tespit etmiştir. ÇİD Acinetobacter spp.…”
Section: Discussionunclassified
“…Son yıllarda kolistin kullanımının artması ile birlikte kolistin direnci raporlanmaya başlanmıştır. Yapılan çalışmalarda kolistin dirençli A.baumannii suşlarında, bazı antibiyotiklerin kolistin ile kombinasyonunun sinerjistik etkili olduğu gösterilmiştir (6,21,28) . Kombinasyon tedavilerinde karbapenemler gibi bakteri hücre duvarına etki eden antibiyotiklerin yanı sıra, sıklıkla rifampin ve sulbaktam da tercih edilmektedir.…”
Section: Introductionunclassified
“…In a study conducted in 2012, it was emphasized that the use of inappropriate antibiotic combination increases CL resistance. 27 Principe et al 7 for the first time reported that they have noticed the synergy between TGC and CL by TK method in one A. baumannii isolate. In two studies conducted by CB method in TGC-CL combination 28 and in TGC-sulbactam, TGC-CL combinations 29 a synergistic effect was observed.…”
Section: Discussionmentioning
confidence: 99%